Where the conflict really lies science, religion, and naturalism - Plantinga, Alvin (New York : Oxford University Press, 2011)
In this long-awaited book, pre-eminent analytical philosopher Alvin Plantinga argues that the conflict between science and theistic religion is actually superficial, and that at a deeper level they are in concord.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 19, 2012).
Keywords: Religion and science; Evolution (Biology) -- Religious aspects -- Christianity; Naturalism -- Religious aspects -- Christianity